Overlooking Saskatchewan minding the gap - Ramsay, Christine, 1958-; Rogers, Randal, 1963- (University of Regina Press, 2014)
In Overlooking Saskatchewan, twenty writers articulate the challenges and the power of the ""gap, "" while revealing how the citizens of Saskatchewan continue to lead the way in the creation of culture and innovation.